Lithoseopsis Mockford (Psocodea: Troctomorpha: Amphientomidae): a new species and first record for South America - Aldrete, Alfonso N. García; Da Silva Neto, Alberto Moreira; Ferreira, Rodrigo Lopes (Zootaxa, 2018)
A species of Lithoseopsis Mockford, from the Brazilian state of Pará, is described and illustrated. It is the first species of Lithoseopsis recorded in Brazil, and the first of that genus known in South America. It differs from all the other species in the genus in details of the forewing pigmentation and spermapore sclerite. A map with the distribution of the Lithoseopsis species is included and two species groups of Lithoseopsis are diagnosed.